Physicochemical properties of rainbow trout (Oncorhynchus mykiss) filet treated with high-voltage electrostatic field under different storage temperatures - Cheng, Yu-Tsung; Huang, Ping-Hsiu; Lu, Wen-Chien; Chu, Sheng-Che; Wang, Pei-Ming; Ko, Wen-Chien; Li, Po-Hsien (Frontiers in Sustainable Food Systems, 2023)
The post-mortem rigid of farmed rainbow trout (Oncorhynchus mykiss) affects the texture of the meat and might even be risky for microorganisms, undermining the popularity of frozen filets among consumers. This study investigated the importance of different conditions (0°C, 4°C, and 25°C for 0–4 days) and physicochemical characteristics of rainbow trout filet storage on fish’s characteristics, freshness, quality, and shelf-life. Results showed that the fish easily underwent rigor mortis and resolution of rigor mortis when stored at 25°C. However, rigor mortis was more likely to occur under storage at 0°C than at 4°C [with 100 kV/m high voltage electrostatic fields (HVEF)] due to low-temperature stimulation, but resolution of rigor mortis began to appear after 24 h of storage at either temperature. The protein solubility and gel strength of fish stored at 25°C continued to decrease due to thermal denaturation, and those of fish stored at 4°C and 0°C also showed a decrease owing to rigor mortis and then an increase when rigor mortis disappeared. The K values increased rapidly at 25°C and reached 61% at 14 h. Under storage at 4°C and 0°C, the K values only slightly increased before resolution of rigor mortis. However, the K-values did not exceed 40% for 4 days post-resolution of rigor mortis. Differential Scanning Calorimetry analysis and tissue sectioning showed that protein denaturation and separation between muscle fibers persisted during storage at various temperatures, most notably at 25°C. It is important to note that storing at 0°C for 96 h did not result in any significant changes in the molecular protein composition. Moreover, the muscle tissue remained in excellent condition compared to storage at 25°C and 4°C. Additionally, there was no significant difference in the total viable count (TVC) and psychrophilic bacteria between storage at 0°C and 4°C, considered safe for food consumption. These promising findings are conveyed in a circular economy based on the food industry, particularly adequate raw materials, stable prices, measures to reduce food loss and waste, and contributing to developing efficient, diverse, and sustainable food processing systems.